The Comparison of Conceptual Understanding Between Secondary School Students and Pre-Service Physics Teacher in Direct Current Electric Circuit (Department of Physics, Faculty of Mathematics and Natural Sciences, 2019)
This study is aimed to compare the understanding of the concepts of secondary school students (junior and senior high school) and pre-service physics teachers in direct current electric circuits. This research was survey research using the quantitative descriptive method. The results showed that there were no significant difference among the junior high school, senior high school, and pre-service physics teacher students with the categories classified as sufficient for junior high school and pre-service physics teacher. However, senior high school students were still relatively weak. The difficulties were found in interpreting formulas and conceptual errors. This research provides practical benefits to the concept of electrical circuits, especially about the low mastery of student’s concepts. The same mistakes at every level of education showed that there are misconceptions that are difficult to eliminate. It is needed to have more effort to master the concept deeply.